THE SHORTEST PATH PROBLEM IN LOGISTICS: THE SHORTEST PATH PROBLEM IN LOGISTICS - Bogdanov, Andrey (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The shortest path problem is one of the fundamental network flow problems. A large number of problems from diverse areas such as routing in telecommunication networks are an intrinsic part of this problem. The report examines different algorithms to solve this major problem for logistics.